Răspuns :
Răspuns:
Explicație pas cu pas:
10.
a) 8 x + 1 = 5 x - 5
8 x - 5 x = - 5 - 1
3 x = - 6
x = ( - 6 ) : 3
x = - 2 ∈ Z
____________________________
b)
- 4 x + 10 = 10 - 2 x
- 4 x + 2 x = 10 - 10
- 2 x = 0
x = 0 ∈ Z
___________________
c)
- 3 x + 5 = - 9 x + 4 x
- 3 x + 5 x = - 5
2 x = 5
x = 5/2 ∉ Z ( ecuatia nu are ca solutie unh nr. intreg )
__________________________________________
d)
2 ( x + 1 ) = 6
x + 1 = 6 : 2
x = 3 - 1
x = 2 ∈ Z
_____________
e)
5( x - 1 ) = 2 x + 7
5 x - 5 = 2 x + 7
5 x - 2 x = 7 + 5
3 x = 12
x = 12 : 3
x = 4 ∈ Z
______________
f)
3( x + 2 ) = 2( x + 4 )
3 x + 6 = 2 x + 8
3 x - 2 x = 8 - 6
x = 2 ∈ Z
_______________
g)
6 = 4( x + 1 ) - 2 ( x + 2 )
6 = 4 x + 4 - 2 x - 4
6 = 2 x
x = 6 : 2
x = 3 ∈ Z
__________
h)
4 = 5( x + 1 ) - 6
4 = 5 x + 5 - 6
4 = 5 x - 1
5 x = 4 + 1
x = 5 : 5
x = 1 ∈ Z
_______________
i)
3( 2 x - 5 ) = 6( x - 1 ) - 9
6 x - 15 = 6 x - 6 - 9
6 x - 6 x = - 15 + 15
0 = 0, ∀ x ∈ Z